EFFECT OF RETURN ON ASSETS (ROA), DEBT TO ASSETS RATIO (DAR), AND CURRENT RATIO (CR) ON STOCK PRICE - Elizabeth Elizabeth; Adrie Putra (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze the effect of Return on Assets (ROA), Debt to Assets Ratio (DAR) and Current Ratio (CR) on the stock prices of real estate companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Return on assets (ROA) is measured by profit before interest tax, depreciation and amortization of total assets. The debt-to-assets ratio (DAR) is measured by total liabilities divided by total assets, and the current ratio (CR) is measured by total current assets divided by total current liabilities. So far, the stock price is measured by the closing price. The method used is purposeful sampling. The samples used in this study were 31 real estate and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2016-2020. The type of data is secondary data from financial reports and annual reports. The data analysis method used in this study is multiple linear regression analysis. The results of hypothesis testing show that simultaneously return on assets (ROA), debt to assets ratio (DAR) and current ratio (CR) have a significant effect on price.share. Partly, only return on assets (ROA) has a significant effect on stock prices. Meanwhile, the partial Debt to Asset Ratio (DAR) and Current Ratio (CR) have no significant effect on stock prices.